2017
DOI: 10.1002/jsfa.8726
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of dietary polyphenols from black soybean seed coats on islet and renal function in streptozotocin‐induced diabetic rats

Abstract: Long-term intervention with BSC at a low dose of polyphenols plays a role in controlling blood glucose and lipids levels by promoting insulin secretion and restoring islet β-cell function, the same as BSCP. These benefits are accompanied by their potential protection of diabetic renal dysfunction. BSCP is mainly responsible for the antidiabetic effect of BSC. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previous studies identified anthocyanins and procyanidins as the two main types of polyphenols and described their antidiabetic effects. Qiu et al [92] demonstrated that the phenolic-enriched crude extract increased the concentrations of serum insulin and GLP-1 in streptozotocin-induced diabetic rats after 8 weeks of treatment. However, they did not identify any specific compound in the extract.…”
Section: Natural Products As Stimulants Of Glp-1 and Gip Secretionmentioning
confidence: 99%
“…Previous studies identified anthocyanins and procyanidins as the two main types of polyphenols and described their antidiabetic effects. Qiu et al [92] demonstrated that the phenolic-enriched crude extract increased the concentrations of serum insulin and GLP-1 in streptozotocin-induced diabetic rats after 8 weeks of treatment. However, they did not identify any specific compound in the extract.…”
Section: Natural Products As Stimulants Of Glp-1 and Gip Secretionmentioning
confidence: 99%
“…Peony total glucosides prevent renal tubular interstitial damage in rats with diabetic nephropathy and delay the development of diabetic nephropathy [37]. HEI DOU reduces blood sugar, blood lipids, serum creatinine, and blood urea nitrogen in streptozotocin (STZ)-induced diabetic rats [38], and long-term low-dose HEI DOU protects diabetic renal insu ciency [39]. Although, the effects of individual components of QBYSF have been examined in diabetic murine models and in patients, the mechanism of QBYSF on diabetic kidney disease is not clear yet.…”
Section: Introductionmentioning
confidence: 99%